PENGARUH BRAND IMAGE, KUALITAS PELAYANAN DAN DISKON TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO EIGER DI SITUBONDO - Suherman, Aldy Kurniawan; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Indonesia is a country that has very abundant wealth, one of which is the beautiful natural panorama from the sea to the mountains. With increasing interest in nature tourism, the need for outdoor equipment has also increased. Companies providing outdoor equipment face stiff competition, both from local and international manufacturers. One example of a successful company in this sector is PT. Eiger Multi Industrial Products. The aim of this research is to analyze the influence of brand image, service quality and discounts on repurchase intention, through consumer satisfaction as an intervening variable at the Eiger Store in Situbondo. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that brand image has a significant positive effect on consumer satisfaction. Service quality has a significant positive effect on consumer satisfaction. Discounts have a positive but not significant effect on consumer satisfaction. Brand image has a significant positive effect on repurchase intention. Service quality has a positive but not significant effect on repurchase intention. Discounts have a significant positive effect on repurchase interest. Consumer satisfaction has a significant positive effect on repurchase intention. Brand image has a positive but not significant effect on repurchase intention through consumer satisfaction. Service quality has a positive but not significant effect on repurchase intention through consumer satisfaction. Discounts have a positive but not significant effect on repurchase intention through consumer satisfaction.